Possibilities for growing queen palm (Syagrus romanzoffiana) in Argentina as a biodiesel producer under semi-arid climate conditions - Falasca, Silvia Liliana (2012)
Syagrus romanzoffiana is a palm native to Argentina, where it is known by the name 'Pindó'. This palm extends from the Misionera Forest through the gallery Forest, being the Parana Delta area the southern limit of dispersion. In this area, the large volumes of water from the rivers create a moderating effect, reducing the daily temperature range and the days of frosts. The aim of this study was to delimit the Argentina agro-climatic suitable area for the development of this crop as a potential biodiesel-producing species, using biophysical limits observed in our country and elsewhere in the world where the plant is grown. For a possible zoning in Argentina, agro-climatic indexes were obtained from monthly values of temperatures and precipitations from all the weather and agro-meteorological stations of the country, for the period 1971-2010. Afterward, maps with the thermal and hydric limits were superposed to define the probable areas for the crop. © 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.